Analysis of Primary Science Teachers' Lesson Plans on Their Awareness of Local Content in Lombok, Indonesia - Lalu Usman Ali; Suranto Suranto; Meti Indrowati (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
Integrating local content into learning is important for connecting the material to students' daily lives, especially in science education. The use of local knowledge can enhance students' understanding and appreciation, but its application still varies across different schools. This study aims to analyze primary school science teachers' understanding of the application of local content in science learning and to evaluate the extent to which this is applied in lesson planning in East Lombok Regency. Additionally, this research also identifies the constraints encountered in its implementation. This study uses a descriptive qualitative design with data collection methods including questionnaires, observation, RPP analysis, and in-depth interviews to explore understanding, perspectives, and challenges related to the implementation of local content. The integration of local content into science learning in five primary schools and madrasahs in East Lombok remains limited, with only about 18% of grade 5 and 11% of grade 6 material covering local contexts. The main discussion points include limited resources, lack of training, and a rigid curriculum. Reliance on standard textbooks and national policies also hinders the adaptation of materials to the local context. The integration of local content into science learning remains low. Professional development for teachers, increased curriculum flexibility, and the provision of appropriate resources are necessary. Future research could explore strategies to strengthen the integration of local knowledge in science learning.